THE FACTOR EFFECT OF HOSPITAL SERVICES, MEDICAL STAFF QUALITY AND HOSPITAL SERVICE QUALITY ON INDONESIAN PATIENT MEDICAL TREATMENT INTENTION IN SINGAPORE - Jony Oktavian Haryanto; Ollivia Ollivia (Jurnal Ilmiah Ekonomi Bisnis, 2009)
Health was valuable assets. Recently, medical treatment has become a new business prospect. Therefore, the health service providers are trying to be able to catch new patients and maintain loyalty of their existing patients. The intention factors of Indonesian patients to take a medical treatment in Singapore are: (1) Factor of hospital services, (2) Quality of medical staff, and (3) Service quality of the hospitals. This research is aimed to analyze the determinant factors of patient intention to take medicine in Singapore. Data were collected using valid and reliable Likert’s scale questionnaire. Sample size used in the study is 100 and data is analyzed using multiple regressions method. The factor of hospital services does not affect the intention of Indonesian patient to take medical treatment in Singapore. The quality of medical staff and factor service quality of hospitals affect the intention of Indonesian patient to take a medical treatment.Key word: hospital services, medical staff quality, hospital service quality